Variation in wood physical and anatomical properties of anjily (Artocarpus hirsutus LAM.) grown in different agro-climatic zones of Thrissur district, Kerala - Swagatika Sahoo (Department of Wood Science, College of Forestry, 2015)
A study entitled “Variation in wood physical and anatomical properties of Anjily (Artocarpus hirsutus Lam.) grown in different agro-climatic zones of Thrissur district, Kerala” was conducted in the College of Forestry, Kerala Agricultural University, Vellanikkara, Thrissur during the period 2015-2017. The present investigation was conducted with the objective to assess the variation in wood anatomical and physical properties of anjily (Artocarpus hirsutus Lam.) grown in different agro-climatic zones (Coastal sandy, Central mid land and Malayoram) of Thrissur district, Kerala and to compare the anatomical and physical property of wood between plantations and homesteads. Samples from anjily trees were selected from the three agro-climatic zones of Thrissur district following stratified random sampling technique. The experimental materials were collected from three agro-climatic zones (9 Costal sandy + 9 Central midlands + 9 Malayoram) which also include trees from three girth classes viz., 50- 100 cm, 100-150 cm. and more than 150 cm. Wood samples of three trees were collected from each girth class. Wood samples were also collected from three plantations in Thalassery taluk of Kannur district. Analysis revealed that some of the anatomical properties were significantly different between girth classes across three agro-climatic zones. Basic density, moisture content, heartwood colour, vessel frequency, vessel area, vessel diameter, ray width, fibre wall thickness and fibre lumen diameter did not show significant difference across three agro-climatic zones. Ray frequency, ray height, ray width and fibre lumen diameter showed significant difference between three girth classes across the zones. Analysis revealed that there was significant differences in vessel frequency, vessel diameter, vessel length, ray width, fibre length, fibre lumen diameter, moisture content and basic density between homesteads and plantation. Ecoanatomical characters like vulnerability index and vessel mesomorphy were also analysed and vulnerability index was found to be highest in central mid land. Mesomorphy values of anjily wood indicated that it was mesic in nature. Correlation analysis also showed that basic density was positively correlated with moisture content, ray height, fibre length and fibre wall thickness. The wood properties of anjily was also found to be comparable to teak wood in various aspects